2022
DOI: 10.3390/sym14091760
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Blockchain in the Healthcare Sector: Application and Issues

Abstract: The emergence of blockchain technology makes it possible to address disparate distributed system security concerns in formerly ridiculous practices. A key factor of this ability is the decentralization of the symmetrically distributed ledgers of blockchain. Such decentralization has replaced several security functionalities of centralized authority with the use of cryptographic systems. That is, public or asymmetric cryptography is the key part of what makes blockchain technology possible. Recently, the blockc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…In [34], [35], the use of electrocardiogram (ECG) signals for the medical image encryption (ImgEnc) technique is proposed. It will use the generalized Arnold and chaotic logistic maps (Cat Map).…”
Section: Discussion Of Findings and Discussionmentioning
confidence: 99%
“…In [34], [35], the use of electrocardiogram (ECG) signals for the medical image encryption (ImgEnc) technique is proposed. It will use the generalized Arnold and chaotic logistic maps (Cat Map).…”
Section: Discussion Of Findings and Discussionmentioning
confidence: 99%
“…The application of blockchain technology in Electronic Health Records (EHRs) is a relatively new and rapidly evolving field, as evidenced by the significant number of publications dedicated to this topic. A recent analysis conducted by Google Scholar identified 2,750 new items published in 2021 and 2022 alone, indicating the growing interest in this area and the need to explore its potential [18]. Numerous studies and surveys have been conducted to present the current state of the art in BT-based EHR systems, shedding light on their benefits, limitations, and open challenges.…”
Section: Related Workmentioning
confidence: 99%
“…There are also review articles specifically focused on one area of interaction, for instance, electronic healthcare record systems [23] or articles addressing the readiness assessment of blockchain applications in healthcare [24]. Use cases were grouped by healthcare issues as well as blockchain characteristics in [25,26], and a well-summarised map of healthcare problems and blockchain opportunities can be found in [27]. A list of start-up companies offering blockchain healthcare solutions can be found in [28].…”
Section: Overview Of Blockchain In Healthcarementioning
confidence: 99%
“…Blockchain technology made it possible to minimize dental session time, It is of note that this framework is not a product of reviewing the existing blockchain in dentistry literature due to the amount of research being very limited and not all possible areas of applications being identified. Following the guidelines of a conceptual study, which could bridge existing theories, link work across disciplines, provide multi-level insights and broaden the scope of our thinking, the following sessions and possible applications are summarised based on bridging the specific needs of dentistry to relevant blockchain properties, the current strands of the framework are grouped based on the existing literature of blockchain in healthcare [25][26][27], our coauthors' knowledge and day to day work experience as dental professionals, as well as our continuous research in big data, blockchain as well as other relevant technological advancements and their interactions with other sectors.…”
Section: Patients' Digital Health Recordsmentioning
confidence: 99%